Algorithmic Management in the Platform Economy - David Stark; Ivana Pais (Journal of Economic Sociology, 2021)
The platform model is the distinguishing organizational form of the early decades of the twenty-first century. Whereas actors in markets contract, hierarchies command, and networks collaborate, platforms co-opt assets, resources, and activities that are not part of the firm. As a distinctive organizational form, the platform model confronts a distinctive managerial challenge: how to manage value-creating activities that are undertaken on the platform but not in the firm? In a triangular geometry, platform owners co-opt the behavior of providers and users, enrolling them in the practices of algorithmic management without managerial authority having been delegated to them. Acting on their own behalf, the ratings and other activities of providers and consumers are algorithmically translated into rankings and other calculating devices that circulate through feedback loops that are twisted rather than circular. Algorithmic management involves a peculiar kind of cybernetic control because at each fold of the feedback loop accountability can be deflected and denied. Whereas Scientific Management in the early twentieth century offered a legitimating principle for the growth of a new managerial class, algorithmic management in the early twenty-first century is reshaping the managerial class. Its power asymmetries at the organizational level are related to coalitions at the regulatory level in which platform owner and investors are in alliance with platform consumers.